A controversial campaign: François Fillon and the decline of the centre-right in the 2017 presidential elections. (2nd October 2017) - Lees, David
Abstract: In the first round of the 2017 French presidential elections, the centre-right candidate François Fillon came third, with 19.94% of the vote. During a campaign mired in controversy over the alleged use of taxpayer money to pay for 'fake' jobs for Fillon's wife and two of his children, Fillon refused to resign the candidacy of the centre-right Les Républicains party, having seen off both Nicolas Sarkozy and Alain Juppé in the primaries. This article examines the key aspects of Fillon's campaign, with particular reference to his economic and social policies and the controversy surrounding the corruption allegations. The article argues that Fillon's third-place result can be attributed to a squeeze on the traditional centre-right vote from both the Front national's Marine Le Pen and from the emergence of the eventual victor, the centrist candidate Emmanuel Macron. Where once Fillon was the favourite to take the presidency, the article argues that Fillon's failure to make it through to the second round was down in part to concerns over corruption, but can also be explained by his limited appeal beyond his core electorate, in steep contrast to his leading rivals, especially Macron.